Neonatal Maternal Separation Modifies Proteostasis Marker Expression in the Adult Hippocampus - Sierra-Fonseca, Jorge A.; Hamdan, Jameel N.; Cohen, Alexis A.; Cardenas, Sonia M.; Saucedo, Sigifredo; Lodoza, Gabriel A.; Gosselink, Kristin L. (Frontiers in Molecular Neuroscience, 2021)
Exposure to early-life stress (ELS) can persistently modify neuronal circuits and functions, and contribute to the expression of misfolded and aggregated proteins that are hallmarks of several neurodegenerative diseases. The healthy brain is able to clear dysfunctional proteins through the ubiquitin-proteasome system (UPS) and the autophagy-lysosomal pathway (ALP). Accumulating evidence indicates that impairment of these pathways contributes to enhanced protein aggregation and neurodegeneration. While stress is a known precipitant of neurological decline, few specific mechanistic links underlying this relationship have been identified. We hypothesized that neonatal maternal separation (MatSep), a well-established model of ELS, has the ability to alter the levels of UPS and ALP components in the brain, and thus has the potential to disrupt proteostasis. The expression of proteostasis-associated protein markers was evaluated by immunoblotting in the hippocampus and cortex of adult Wistar rats that were previously subjected to MatSep. We observed multiple sex- and MatSep-specific changes in expression of proteins in the ALP, mitophagy, and UPS pathways, particularly in the hippocampus of adult animals. In contrast, MatSep had limited influence on proteostasis marker expression in the cortex of adult animals. Our results indicate that MatSep can selectively modify the intracellular protein degradation machinery in ways that may impact the development and progression of neurodegenerative disease.